Examining the effect of Directed Activity Related to Texts (DARTs) and gender on students' achievement in qualitative analysis in chemistry - Shamsulbahri, Mohamad Mahathir; Zulkiply, Norehan (Universiti Utara Malaysia Press, 2021)
Purpose: The present study examined the effect of Directed Activity Related to Texts (DARTs) and gender on students’ achievement in Chemistry. The present study focused on the qualitative analysis component of Chemistry which has been perceived as being most difficult among students.Methodology: The study involved 120 form four science stream students from two local fully residential schools. In a quasi-experiment, participants studied the qualitative analysis of salt topic using one of these three instructional methods: Experiment, DARTs, and Combination of Experiment and DARTs; and later their knowledge about salt was tested. Findings: Results of a two-way independent ANOVA performed on the experiment data revealed a significant main effect of Instructional method—the mean scores for the combined method group was the highest, followed by the DARTs group and then the Experiment group. Further analysis using an independent t-test showed that the difference in mean scores between the DARTs and Experiment groups was significant. It is argued that participants’ learning in the Combined method group might have been enhanced by the DARTs instructional method. The effect of gender and the interaction effect between the variables were not significant.Significance: The present findings provides experimental evidence regarding the role of the DARTs instructional method in enhancing qualitative analysis learning in Chemistry. The present findings also provide insights to educators on DARTs as an alternative methods of teaching and learning qualitative analysis topics in Chemistry.